DHIKR THERAPY AND DEEP BREATHING RELAXATION TECHNIQUES AS ANXIETY THERAPY IN PATIENTS WITH POST-PULMONARY TUBERCULOSIS TREATMENT - Yuniartika, Wachidah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Patients with post-tuberculosis disease having difficulties in conducting activities cause them to be anxious about their condition. Rehabilitative efforts that are likely to provide include dhikr therapy and deep breathing relaxation. Dhikr and deep breathing relaxation are beneficial for drawing closer to Allah SWT, reducing anxiety, and being relaxed. This study aimed to determine the effectiveness of dhikr therapy and deep breathing relaxation to reduce anxiety in patients with post-tuberculosis treatment. This research is quantitative with a pre-test and post-test with a control group design, conducted at the Baki Sukoharjo Health Center from August to October 2022. The sample consisted of 60 respondents. Inclusion criteria are as follows: Patients with post-tuberculosis treatment, suffering from moderate and mild anxiety, Muslim, age 60 years, not suffering from complications, and not receiving anxiety medication therapy. The results showed that the mean of the intervention group was 32.20, and the post-test was 17.30, with P-value was 0.001. The pre-test of the control group obtained a mean of 37.77 and the post-test was 24.73, with P-Value was 0.005. Dhikr therapy as an intervention group and deep breathing therapy as a control group can reduce anxiety.